IMPLEMENTASI TEKNIK BERMAIN PADA PROGRAM KAMPUS MENGAJAR ANGKATAN 6 DALAM MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SISWA SD NEGERI 3 MAYONGLOR: Implementation of Playing Techniques In Campus Teaching Program For Force 6 in Improving Students' Literacy And Numeration Skills In Primary School 3 Mayonglor - Diner, Lispridona; Indriyani, Eka; Akhiroh, Elok Nur; Nafi’ah, Fiki Zakiyatun; Sari, Shelly Novita; Firdaus, Zuhairina (Anterior Jurnal, 2024)
Education in Indonesia, especially at the elementary level, still faces big challenges, especially in terms of literacy and numeracy. This difficulty is more pronounced in remote areas, such as what happened at SD Negeri 3 MayongLor, Jepara. Therefore, the Ministry of Education and Culture (Kemendikbud) launched the Class 6 Teaching Campus Program to improve the literacy and numeracy skills of students in these schools. The aim of this research is to determine the effectiveness of implementing playing techniques, with a focus on improving students' literacy and numeracy skills and knowing the advantages and disadvantages of playing techniques in the Class 6 Teaching Campus program at SD Negeri 3 MayongLor. The research method used was quantitative and qualitative, involving 30 students as research subjects. Data was collected through observations, questionnaires, tests and documentation during the three months of program implementation. The results of the questionnaire show that 60% of students strongly agree that learning literacy and numeracy is fun, 66% of students strongly agree and agree that they are motivated to learn literacy and numeracy through playing techniques, 53% of students strongly agree and agree that they can master literacy and numeracy effectively and 51% Students strongly agree that they can master literacy and numeracy through digital-based play techniques.  It can be concluded that there is effectiveness in improving literacy and numeracy learning outcomes through techniques in the Class 6 Teaching Campus Program at SD Negeri 3 MayongLor.